Uncovering the motivations of sport tourism volunteers: Insights from the Athens Marathon - Fysentzidis, Michael; Strigas, Athanasios; Ntasis, Lazaros (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to uncover the underlying motivations and goals of sports tourism volunteers who dedicated themselves to the Athens Marathon. It presented a comprehensive and timely examination of sport tourism by employing qualitative research methods, such as interviews and participant observation. The study involved 18 participants who were part of the “Athens Marathon, the Authentic” in Greece in 2020. A qualitative online survey was developed as part of a longitudinal study and encompassed a set of open-ended inquiries addressing travel planning, motives underlying sport volunteer, and prior volunteer engagements. The findings of this study shed light on the motivations and goals of tourism volunteers participating in the Athens Marathon, revealing three primary motives: egoism, leisure, satisfaction, and acknowledgment of expertise. Egoistic motives were prominent among volunteers, driven by desires for personal recognition and achievement through their involvement in a prestigious event. Leisure motives underscored the integration of travel and recreational interests with volunteerism, enhancing the fulfilling experiences of volunteers. Satisfaction and acknowledgment of expertise were also substantial, with volunteers deriving fulfillment from their contributions and seeking recognition for specialized skills in areas such as event management and logistics. These findings contribute by emphasizing the importance of tailored volunteer engagement strategies for enhancing participant satisfaction and event success.